2015
DOI: 10.13080/z-a.2015.102.025
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium effects on mineral accumulation, antioxidant defence system and gas exchange in cucumber

Abstract: The effects of different concentrations (10, 50, 100 and 500 μM) of cadmium (Cd) on manganese (Mn) and iron (Fe), lipid peroxidation, activities of antioxidant enzymes and photosynthetic function were investigated in hydroponically grown cucumber (Cucumis sativus L.). Results indicated that cadmium was accumulated primarily in roots. In the roots and shoots, the cadmium content increased with the increasing cadmium concentrations, and induced decrease of manganese significantly (P < 0.005). The levels of iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
6
8
0
Order By: Relevance
“…In general, selected heavy metal solutions demonstrated a concentration-dependent inhibition on seedling growth. A similar phenomenon has been reported in a previous study on phytotoxicity of heavy metals on plants [16,[39][40][41][42]. Mahmood et al [43] (p. 451) found that the effects of Cu on root length of rice and wheat seedlings were more pronounced than that of Pb and Zn, while the root length of all crop seedlings was significantly affected by increasing Cu, Pb and Zn.…”
Section: Discussionsupporting
confidence: 84%
“…In general, selected heavy metal solutions demonstrated a concentration-dependent inhibition on seedling growth. A similar phenomenon has been reported in a previous study on phytotoxicity of heavy metals on plants [16,[39][40][41][42]. Mahmood et al [43] (p. 451) found that the effects of Cu on root length of rice and wheat seedlings were more pronounced than that of Pb and Zn, while the root length of all crop seedlings was significantly affected by increasing Cu, Pb and Zn.…”
Section: Discussionsupporting
confidence: 84%
“…Plants possess a number of antioxidant systems that protect them from oxidative damage [49]. These defensive systems are composed of enzymatic scavengers of activated oxygen such as SOD, POD, and CAT [50].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of H 2 O 2 was estimated by measuring the absorbance of the titanium-hydroperoxide complex and using a standard curve plotted with a known concentration of H 2 O 2 . Oxidative damage to lipids was determined by measuring the content of malondialdehyde (MDA), prepared in 10% trichloroacetic acid containing 0.65% 2-thiobarbituric acid (TBA) and heated at 95°C for 25 min, and then quickly cooled (Sun et al, 2015). MDA content was calculated by correcting for compounds other than MDA which absorb at 532 nm by subtracting the absorbance at 532 nm of a solution containing plant extract incubated without TBA from an identical solution containing TBA.…”
Section: Measurement Of Hydrogen Peroxide (H 2 O 2 ) and Malondialdehmentioning
confidence: 99%